THE USE OF REMOVABLE FUNCTIONAL ORTHODONTIC APPLIANCES IN GROWING PATIENTS - Loredana Golovcencu; Gabriela Luminita Geletu; Catalina Iulia Saveanu; Vasilica Toma; Georgeta Zegan; Daniela Anistoroaei (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study Functional appliances have been used for over 100 years in orthodontics to correct Class II malocclusion and since then many different appliances were developed in order to correct muscular behaviour and skeletal imbalances during growth. Material and methods Three different types of removable functional appliances most used in clinical practice are discussed considering their indications, actions, advantages and disadvantages. Results Recent clinical research is focused whether they really have a lasting influence on facial growth, the extent of mandibular growth in class II orthodontic patients with retrognathic mandible, the proper timing for treatment with functional appliances and which are the factors that influence the obtained results. The article discusses the clinical effectiveness of these appliances, the orthopaedic effect that can be useful during growth period for the correction of sagittal and transverse arch discrepancies, their use and their limitations. Conclusions The removable functional appliances might be useful tools to correct skeletal imbalances, especially for class II malocclusion division 1 patients if they are applied during mixed dentition and early permanent dentition period, but they hardly depend by the patient's compliance in appliance wear.